Supported foam copper catalysts for methanol selective oxidation; XVI International Conference on Chemical Reactors CHEMREACTOR-16, Berlin, Germany, December 1-5, 2003 - Pestryakov A. N. Aleksey Nikolaevich (2003, 2003)
Structural, mechanical, gas-dynamic and catalytic properties of copper catalysts supported on foam ceramics have been studied. Due to the three-dimensional open-porous cellular structure the foam catalysts have high gas permeability, mechanical strength, and low density. Catalytic activity and selectivity of the foam catalysts in the process of oxidation of methanol to formaldehyde exceed the characteristics of the conventional crystalline and granulated catalysts of the same composition. Different electronic states (ions, charged cluster, crystals) of copper on the catalyst surface have been studied by the method of UV-visible spectroscopy.